2016
DOI: 10.1016/j.jemermed.2015.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Dual Learning in an Emergency Medicine Clerkship Improves Student Performance

Abstract: , Abstract-Background: The emergency department (ED) is an ideal environment to teach learners about the ''undifferentiated patient.'' Student learning may be inconsistent because of inherent variability in the ED. Previous research has suggested that standardizing the emergency medicine (EM) clerkship by implementing didactics and requiring students to see patients with particular chief complaints improves educational outcomes. Objective: To compare knowledge acquisition after a new curriculum to the traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Understanding that scholarly work can improve clinical skills may encourage program leadership to deepen this experience for all trainees, supporting a multimodal approach to education, which can augment learning. 31 This study also demonstrated that scholarly work impacts career planning and achievement. Our participants felt a strong sense that their scholarly work in residency informed their future career aspirations.…”
Section: Discussionmentioning
confidence: 62%
“…Understanding that scholarly work can improve clinical skills may encourage program leadership to deepen this experience for all trainees, supporting a multimodal approach to education, which can augment learning. 31 This study also demonstrated that scholarly work impacts career planning and achievement. Our participants felt a strong sense that their scholarly work in residency informed their future career aspirations.…”
Section: Discussionmentioning
confidence: 62%
“…A total of 434 papers and abstracts satisfied the search criteria, and 61 papers met the inclusion criteria . The authors scored these 61 manuscripts, and the 10 highest scoring quantitative and two qualitative articles are reviewed below, in alphabetical order by first author's last name.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental (hypothesis testing) studies declined in 2015 from 36% of the total to 15% of all reviewed studies . Notably, four of these were articles highlighted for excellence and represent 15% of the featured studies. Six studies (10%) involved qualitative methodology of which two were highlighted .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations